Relationships between Social Capital and regional development in Europe: a close examination - Paolo Rizzi; Roberta Pianta (European Regional Science Association (ERSA), 2011)
The study of the Social Capital and its relationships with the development is a topical subject. The theme has not an exactly definition yet. Some proofs at national and regional levels in Europe show interactions between the Social Capital and the economic growth and the labour market. From them, the paper aims to analyze these results, trying to specify the significances. Applying the Principal Components Analysis to several interesting single variables (coming from the European Values Survey database), some macro-variables were created and inserted in regressions, producing partial results. These macro-components summarize the elements of the Social Capital and they are broken down as single variables. A benchmarking between subjective variables and quantitative ones is realized to explain the concept of the Social Capital, with the aim of consider the individual and collective insight and the concrete effects of this multi-dimensional idea. To fulfill the analysis, a remark is faced on the relationships between the Social Capital and the development, as the causality between them deserves further examinations.
Keywords: 330